(untitled) (Zaporizhzhia Historical Review, 2021)
In the article the changes of looks of political elite of Hetmanshina in relation to power of hetman are explored, related to the Russian policy in Ukraine in 1654-1657. Keywords: hetman form of rule, contractual articles, imperial’s government, cossacks petty officer.